2009
DOI: 10.3945/ajcn.2008.25970
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the transcriptome of abdominal subcutaneous adipose tissue in response to short-term overfeeding in lean and obese men

Abstract: Differential expression of these 6 genes may represent a protective mechanism at the molecular level in lean subjects in response to an energy surplus. These genes represent valuable candidates for downstream studies related to obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
7
32
2
Order By: Relevance
“…Importantly, we technically validated our microarray data on all five analysed genes using qPCR. Additionally, the overlap in SAT gene expression data between our study and previous short-term overfeeding studies further supports the biological significance of our data [18,19]. Nevertheless, small changes in gene expression should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Importantly, we technically validated our microarray data on all five analysed genes using qPCR. Additionally, the overlap in SAT gene expression data between our study and previous short-term overfeeding studies further supports the biological significance of our data [18,19]. Nevertheless, small changes in gene expression should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 84%
“…We found a large overlap in the transcriptional response to overfeeding in SAT between our HFO study and two previous short-term (7-14 days) overfeeding studies (ESM Table 6) [18,19].…”
Section: Changes In Sat Expression In Response To Hfosupporting
confidence: 52%
See 2 more Smart Citations
“…Our laboratory and others have shown that changes in nutritional status, such as overfeeding, have major effects on adipose tissue metabolism (19,20), circulating concentrations of adipokines (21), and gene expression profiles (22). A positive energy balance may also influence circulating concentrations of gut hormones, such as PYY, and subsequently affect appetite.…”
Section: Introductionmentioning
confidence: 99%